A SENTENCE IN A LITERARY TEXT (BASED ON THE SIGNIFICANT WORDS OF SHAKARIM KUDAIBERDIULY) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
A text is a unified communication unit with specific content, based on logical, grammatical, and semantic connections. Therefore, it is important to define the structure of a text and the laws of its existence in a specific space and time. The study of both explicit and implicit text-forming units in literary texts is of great importance. In a text, the author uses specific linguistic markers to convey their point of view and specific content. In modern linguistic usage, it is necessary to understand the function of a sentence, a group of sentences that has special content and impact in a literary text. Today's analysis of the linguistics of literary texts is considered in connection with the manifestation of linguistic individuality in cultural, social and national aspects. In this regard, based on the significant words of Shakarim Kudaiberdiuli, the goal is to show the use of the sentence in literary texts and its pragmatic impact on the listener.The linguistic aspect of the analysis of a literary text is of great practical importance in terms of forming one’s own judgments through the perception and understanding of the aesthetic and poetic power of words. Linguistic analysis of text types is based on established methodology. The observation method was used in accordance with the research topic. The importance and necessity of integrating the results of new trends and research emerging in modern linguistics into the text analysis process are great.